Desenvolvimento de microcápsulas de café pelo processo de gelificação iônica: determinação dos compostos bioativos e perfil volátil - Linhares, Caroline Silva (2018)
Coffee is one of the most consumed products in the world and rich in caffeine, so it has a high stimulating power thus helping concentration and better performance of activities. The encapsulation technique gives the product greater durability, since it protects against the external environment besides releasing the encapsulation in a gradual way. The objective of this work was to produce microcapsules of coffee and to study the encapsulation process, verifying the physical-chemical, microbiological changes during 60 days and the effects on the quality of the product using as gelling agent the sodium alginate, in addition to its aromatic profile by gas chromatography. The raw material used to make the microcapsules were samples of arabica coffee grains and the microcapsules were obtained through the ionic gelation technique. Two coffee concentrations were used: 7 g of coffee per 100 ml of water and 14 g of coffee per 100 ml of water. During the storage period, it was possible to verify that the moisture and ash content did not change significantly during the storage time, and that the product with higher concentration had a higher pH, the acid values decreased during the 60 days. The phenolic value found was higher than the literature observed, and had a slight drop during storage. It was also observed the stability of the antioxidants in the different concentrations, besides their high values. The caffeine content had a significant difference between the concentrations studied, and it could be seen that in the case of an encapsulation technique there was a relatively considerable entrapment of this compound. No microbial contamination was observed. In order to determine the volatile coffee and microcapsule profile, 66 volatile compounds were found for all samples at different concentrations, with the main compounds being ethanol, pyridine, 2-methyl-pyridine, 5-methyl-2-furfural, furfuryl acetate, 2- furanmethanol. The gelation encapsulation technique proved to be effective in protecting the compounds with OAV> 1, which are responsible for coffee aroma, such as 3-Ethyl-2,5- dimethylpyrazine, 2-Ethyl-3,5-dimethylpyrazine, 2- Methylbutanal, hexanal. There is a difficulty in finding parameters of comparison for microcapsule of coffee, because this product does not exist in the market, but compared to the result of the coffee in its natural state we can perceive that the product has positive points, therefore it is a promising product to be commercialized.